Polemik Dana Aspirasi Dalam Perspektif Politik Hukum Penganggaran Indonesia - Erawati Erawati (Universitas Sriwijaya, 2020)
In addition to being considered prone to corrupt practices, the existence of aspirational funds is deemed to have deviated from the existing legal corridors of state administration and legislation, bearing in mind that the authority of the DPR which was